Effect of diet and packaging system on the microbial status, pH, color and sensory traits of rabbit meat evaluated during chilled storage. (July 2018) - Cullere, Marco; Dalle Zotte, Antonella; Tasoniero, Giulia; Giaccone, Valerio; Szendrő, Zsolt; Szín, Melinda; Odermatt, Meinrad; Gerencsér, Zsolt; Dal Bosco, Alessandro; Matics, Zsolt
Abstract: The combined effect of two dietary lipid sources (sunflower vs linseed oil) and three packaging methods (PVC film - BAG, modified atmosphere CO2 20% + 80% O2 - MAP, and vacuum - VAC) on the shelf-life (pH, color, microbial count, sensory traits) of rabbit loins was tested at days 1, 4 and 10 of refrigerated storage. Linseed oil did not adversely affect neither the physical or sensory traits, nor the microbiological quality of rabbit meat throughout the shelf-life trial. The three packaging methods were all similarly effective in maintaining the physical and sensory quality of the meat, irrespective of the different dietary lipid sources and thus different susceptibility to oxidation. MAP and VAC were more effective than BAG in preserving rabbit meat hygienic quality, as highlighted by the microbial count analyzed at day 4 of shelf-life ( P  < 0.001). At day 10, the microbiological quality didn't differ between MAP and VAC rabbit meat samples. Highlights: Effect of two diets and three packaging methods on rabbit meat quality were tested. A ten-day shelf-life trial under chilled conditions was planned. 3% linseed oil in rabbit diet did not worsen meat microbial/sensory quality. MAP and VAC packaging were the most effective to limit the meat microbial growth. Shelf-life duration of rabbit meat packaged under MAP and VAC should be determined.